Undoing Monogamy : The Politics of Science and the Possibilities of Biology - Willey, Angela, 1978- (Book collections on Project MUSE., 2016)
In Undoing Monogamy Angela Willey analyzes the contemporary science of monogamy, demanding a critical reorientation toward the understanding of monogamy and non-monogamy in the natural sciences, social sciences, and humanities.